Improving the quality control process using the PDCA cycle - Chojnacka-Komorowska, Anna; Kochaniec, Sebastian (Wykorzystanie cyklu PDCA w procesie poprawy jakości wewnętrznej, 2019)
The main purpose of this article is to present the results of research on improving the quality of a finished product by improving the internal control through the use of the PDCA cycle. The research undertaken was carried out by using the case study method supported by the analysis of documentation originating from the surveyed enterprise and the technique of intelligence and observation. Before the study was started, a number of defective finished products was analysed, divided into five main types. Based on the observations made, the disadvantages were assigned to individual work stations and methods of quality improvement were established on each of them. In the next stage the necessary changes were made according to the specifications. The summary of the whole article is a discussion of the results obtained in the field of improving the quality of the finished product in the surveyed enterprise
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 4, s. 69-80
Keywords: quality; internal quality; PDCA; jakość; wewnętrzna kontrola jakości